MANFAAT INFORMASI AKUNTANSI BAGI PEMAKAI POTENSIAL - Camelia Verahastuti (Prodi Ilmu Administrasi Negara, 2015)
The aim of this research is to know the objective of the finance report (business and non-business) as the main component of the conceptual Financial Accounting Standars Board (FASB) .The method of the research is a library one by electronic media and some literature/books . It makes an effort to plug in the accounting by focusing to the investor and creditor as the dominant position .The decisition of them is the one to be served by the information holders through the report. It must be useful for the users and having value or utility to decisition making of them by way of reliabilty and relevance.There are not only investor as well as creditor but also the free riders as the users of the information . The accounting informations covering company wealth, income, and economic events. The finance reports ar expected to help the users to make an economic disicion becaues the high economic rentability and marginal profit motivate the managers to give detailed information .by those will ensure the investor towrds the profitabilty and encaourage compensation towards the managemen.The report of the accounting must be based on the standard opertional procedure .which influences the economic actors which is hoped , therefore , the prosperity distribution will happen through the three particpant namely investor and creditor as intended users, and others as free riders and manajement as reporting entity.The usage of the inforrmation for the investor reserched emperically through the relation of the published ccounting information with the change of the security value of the company will be useful for the assestment of the company concerned.